Losing identity: structural diversity of transposable elements belonging to different classes in the genome of Anopheles gambiae - Fernandez-Medina, Rita D.; Ribeiro, Jose M. C.; Carareto, Claudia M. A. [UNESP]; Velasque, Luciane; Struchiner, Claudio J. (Biomed Central Ltd., 2012)
Background: Transposable elements (TEs), both DNA transposons and retrotransposons, are genetic elements with the main characteristic of being able to mobilize and amplify their own representation within genomes, utilizing different mechanisms of transposition. An almost universal feature of TEs in eukaryotic genomes is their inability to transpose by themselves, mainly as the result of sequence degeneration (by either mutations or deletions). Most of the elements are thus either inactive or non-autonomous. Considering that the bulk of some eukaryotic genomes derive from TEs, they have been conceived as TE graveyards. It has been shown that once an element has been inactivated, it progressively accumulates mutations and deletions at neutral rates until completely losing its identity or being lost from the host genome; however, it has also been shown that these neutral sequences might serve as raw material for domestication by host genomes.Results: We have analyzed the sequence structural variations, nucleotide divergence, and pattern of insertions and deletions of several superfamilies of TEs belonging to both class I (long terminal repeats [LTRs] and non-LTRs [NLTRs]) and II in the genome of Anopheles gambiae, aiming at describing the landscape of deterioration of these elements in this particular genome. Our results describe a great diversity in patterns of deterioration, indicating lineage-specific differences including the presence of Solo-LTRs in the LTR lineage, 5'-deleted NLTRs, and several non-autonomous and MITEs in the class II families. Interestingly, we found fragments of NLTRs corresponding to the RT domain, which preserves high identity among them, suggesting a possible remaining genomic role for these domains.Conclusions: We show here that the TEs in the An. gambiae genome deteriorate in different ways according to the class to which they belong. This diversity certainly has implications not only at the host genomic level but also at the amplification dynamic and evolution of the TE families themselves.
Keywords: Transposable element; LTR; Non-LTR; Class II; Deterioration; Anopheles gambiae